Mecanismos internacionais não-convencionais de proteção do meio ambiente : a prática interamericana - Silva Filho, Lídio Modesto da (2016)
The essay has as object of study the non-conventional mechanisms to protection of human rights. Environmental law is seen as a human right in itself. By analyzing the conceptual evolution of sovereignty, formalized with the historical affirmation of human rights, seeks to demonstrate its relativity and consequent mitigation in favor of these established rights. The principle of sovereignty front of changes that have occurred in international human rights law weakened the classical notion of the sovereign state. The environment is a basic human right which does not have exceptions, and the existence of the conventional and non-conventional mechanisms safety control are they of universal interest. It analyzes the performance of conventional mechanisms established by specific human rights conventions, as well as non-conventional mechanisms, derived as a rule of non-binding instruments. Are studied the global and regional systems of protection and promotion of human rights the ways in which these instrumentalize systems and created tools for achieving the ideal of human rights. The aim is to discuss non-conventional instruments executed at the regional level, with the Organization of American States (OAS) as the main forum to promote dialogue, exchange and cooperation of environmental human rights, which demonstrates the transposition of the conceptual/theoretical to the practical levels.